MENUJU PENDIDIKAN ISLAM BERKUALITAS: Guru Kompeten dan Kurikulum Dinamis - Munawir, Munawir; Laili, Alifa Nur; Pratiwi, Tiara Puspa (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
Islamic education plays an important role in forming a generation with noble character and morals. To achieve this goal, quality Islamic education is needed with competent teachers and a dynamic curriculum. This research uses a literature study method to examine the concept of quality Islamic education, teacher competency, and dynamic curriculum. The research results show that quality Islamic education must be able to answer the challenges of the times. A competent teacher is a teacher who has 4 competency qualifications, namely adequate pedagogical, personal, professional and social competencies. A dynamic curriculum is a curriculum that is able to adapt to current developments and the needs of students.